2011
DOI: 10.1158/0008-5472.can-10-4179
|View full text |Cite
|
Sign up to set email alerts
|

Profound Coordinated Alterations of Intratumoral NK Cell Phenotype and Function in Lung Carcinoma

Abstract: Both the innate and adaptive immune systems contribute to tumor immunosurveillance in mice and humans; however, there is a paucity of direct evidence of a role for natural killer (NK) cells in this important process. In this study, we investigated the intratumoral phenotypic profile and functions of NK cells in primary human tumor specimens of non-small cell lung carcinoma (NSCLC). We used in situ methods to quantify and localize NK cells using the NKp46 marker and we characterized their phenotype in blood, tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
378
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(412 citation statements)
references
References 35 publications
30
378
1
3
Order By: Relevance
“…In addition, we also found that tumor-associated NK cells had significantly decreased expression of NKG2D, NKp46, perforin, and granzyme B as well as increased expression of the inhibitory receptor NKG2A. The results we have examined in murine tumor-associated NK cells correlate well with human studies which have shown that NK cells from human cervical tumors or non-small cell lung carcinoma (NSCLC) display decreased expression of NKp46 and NKG2D 29,30 . In these studies, tumor NK cells were less cytotoxic and displayed a reduced ability to produce IFN-c.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we also found that tumor-associated NK cells had significantly decreased expression of NKG2D, NKp46, perforin, and granzyme B as well as increased expression of the inhibitory receptor NKG2A. The results we have examined in murine tumor-associated NK cells correlate well with human studies which have shown that NK cells from human cervical tumors or non-small cell lung carcinoma (NSCLC) display decreased expression of NKp46 and NKG2D 29,30 . In these studies, tumor NK cells were less cytotoxic and displayed a reduced ability to produce IFN-c.…”
Section: Discussionsupporting
confidence: 79%
“…16,17 Indeed, immunophenotyping studies showed that NK infiltrating tumors cells, exhibited altered effector functions, as shown in breast and lung malignancies. 18,19 NK cell relative anergy correlated with downregulation of their natural cytotoxic receptors. [18][19][20] In addition to the numbers of tumor infiltrating NK cells, NK cell receptor expressions (NKp30 or KIRs) were found to strongly influence the prognosis in several malignancies such as in renal cell carcinoma, 21 GIST, 12 neuroblastoma 13 and acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 96%
“…18,19 NK cell relative anergy correlated with downregulation of their natural cytotoxic receptors. [18][19][20] In addition to the numbers of tumor infiltrating NK cells, NK cell receptor expressions (NKp30 or KIRs) were found to strongly influence the prognosis in several malignancies such as in renal cell carcinoma, 21 GIST, 12 neuroblastoma 13 and acute myeloid leukemia. 22 Our recent studies on NK cells in melanoma patients also indicate the involvement of NK cells in the natural history of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…The distribution of lymphocytes may be differently orchestrated depending on the tumoral architecture. Thus, NK cells are usually found in the stroma of most tumors [28] but can be found in close contact with tumor cells in renal cell carcinoma (RCC) [29]. T cells are located in the core, often referred as the center of the tumor (CT), its invasive margin (IM) [30] and in adjacent lymphoid islets [31].…”
Section: The Immune Microenvironment Is Heterogeneous and Diversementioning
confidence: 99%
“…The case of B lymphocytes is also unclear: they correlate with tumor growth and invasion in murine models [44][45][46][47] but scarce observations associate a B cells signature to good prognosis in several human cancers [48][49][50]. Intratumoral NK cells have been reported to down regulate their activating receptors and to be associated to larger breast [51] and lung [28] tumors, but without clear impact on patients survival. In other cancers, however, NK cell density rather correlates with good prognosis [14].…”
Section: The Immune Contexture Of the Tumor Microenvironment Has A Mamentioning
confidence: 99%